ALIH FUNGSI LAHAN SAWAH DAN PENGARUHNYA TERHADAP PENDAPATAN PETANI DI DESA CACABAN, KECAMATAN CONGGEANG, KABUPATEN SUMEDANG - Gessan Kurnia Dewi; Nur Syamsiyah (Universitas Galuh Ciamis, 2020)
Indonesia's economic growth has increased every year as well as population growth. An increase in economic growth and population growth are pushing increase the need for land. The need for land is increasing but the availability of land is relatively fixed causes competition in land utilization and changing the function of agricultural land into non-agricultural land. Agricultural land conversion into non-agricultural occurred because agricultural land has a low rent. One of the areas experienced agricultural land conversion is Cacaban Village, Conggeang District, Sumedang Regency. Most of population in this village have jobs as farmers, especially in the rice commodity. The increased rice field conversion will affect the income earned by the majority of the population in Cacaban Village. The purpose of this study was to determine its effect on farmer’s income. This study uses a quantitative research design and questionnaires as research instrument. Data analysis in this study used T-test or average different test with SPSS 23. The result showed rice field conversion has a negative effect on farmer’s income, there was a decrease in farmer’s income.